2005
DOI: 10.1097/00008390-200506000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous, ocular and visceral melanoma in African Americans and Caucasians

Abstract: The incidence and age-specific rates of cutaneous, ocular and visceral melanoma were compared in blacks, whites and other ethnic groups using data obtained from the Surveillance, Epidemiology and End Results (SEER) Program of the National Cancer Institute for the years 1973-2001. As the SEER Program is now more mature and includes a larger proportion of minority populations, we thought it important to revisit these observations in more detail. Overall, the rate of cutaneous melanoma was higher in white males b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…The distribution of favored sites of melanoma is sex-dependent: the most common areas were the trunk for men and extremities for women (Tsai et al, 2005). Such specific site-distributions of skin melanoma are often explained by peculiarities of clothing and sun-bathing behaviors between men and women (Elwood et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of favored sites of melanoma is sex-dependent: the most common areas were the trunk for men and extremities for women (Tsai et al, 2005). Such specific site-distributions of skin melanoma are often explained by peculiarities of clothing and sun-bathing behaviors between men and women (Elwood et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Data from the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) program is the most authoritative source for malignant tumor epidemiology, and this information is the best source of malignant tumor incidence rates in the United States [11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27]. We analyzed the incidence of vulvar and vaginal melanomas in various racial/ethnic groups on the basis of the data collected between 1992 and 2005, which consisted of 324 cases of vulvar melanomas and 125 cases of vaginal melanomas with known race and ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…For both Hispanics and African Americans, melanoma incidence is positively associated with the UV index. 5,6,41,42 However, another study showed that melanoma incidence was associated with increased UV index only in NHWs. 43 Possible ethnic differences may exist in the oxidation of melanin and in the release of reactive oxygen species secondary to melanosomal damage, DNA damage, and redox metabolism.…”
mentioning
confidence: 99%